Metronomic photodynamic therapy for deep organ cancer by implantable wireless OLEDs - Yujiro Itazaki; Kei Sakanoue; Katsuhiko Fujita; Izumi Kirino; Kazuhiro Eguchi; Yutaka Miyazono; Ryoichi Yamaguchi; Takasumi Tsunenari; Takao Sugihara; Kenji Kuwada; Naoki Kobayashi; Tsuyoshi Goya; et al. (APL Bioengineering)
Metronomic photodynamic therapy (mPDT) is a method of continuously delivering low-intensity light to a cancer lesion. This approach does not require high-intensity light, enabling the miniaturization of light devices and making them suitable for implantation within the body. However, the application of mPDT to tumors in deep organs such as the liver and pancreas has yet to reach practical implementation. In this study, we developed an mPDT system designed to meet three key requirements deemed essential for practical use: (1) uniform light irradiation throughout the tumor, (2) maintenance of constant light intensity within the body with sufficient operational duration, and (3) avoidance of immunological complications and thermal damage. The newly constructed mPDT system incorporates an ultra-thin organic light-emitting diode (OLED) device and wireless energy transfer technology, allowing it to be designed for implantation in deep organs. In experiments using a rat model of orthotopic hepatoma, the new mPDT system effectively induced widespread cell death deep within the tumor and exhibited high therapeutic efficacy against cancer. This study is the first study to demonstrate that mPDT utilizing a biocompatible and wirelessly powered OLED device has strong anti-tumor effects against parenchymal organ cancers. The findings represent a significant advancement toward the clinical application of mPDT for the treatment of deep organ cancers.